Carry me : a novel - Behrens, Peter, 1954- (Pantheon Books, 2016)
"CARRY ME is told from the perspective of Billy, born to a German father and an Irish mother who are employees on the summer estate of the German-Jewish Baron von Weinbrenner on the scenic Isle of Wight. The book's brilliant narrative twines together the love story of Billy and Karin, the baron's free-spirited daughter, during several crucial months in 1938, and their childhood journey, separately and together, leading up to that 1938 moment when their fates hang in the balance. Billy's backstory takes us through England, Ireland, and Germany, where his family is deported as the political situation in 1930s Europe deteriorates. They find refuge at the Weinbrenners' beautiful home outside Frankfurt, where Billy's father becomes the horse trainer in the baron's famous stables, and the teenage Billy reconnects with the seductively devil-may-care Karin. The two ride horses and shoot bow and arrows in the woods, and share the beloved Winnetou novels of Karl May, whose sere West Texas landscape becomes a powerful beacon in their relationship when they reach young adulthood, suggesting a possible path to freedom as the Germany they once knew is deteriorating rapidly. Billy, with his British passport, schemes to get Karin out of the country, and the reader almost can't breathe, waiting for them to board a boat. Poetic, allusive, and profound, CARRY ME is the true story of Peter's father--brilliantly reimagined as a love story, a historical epic, and a powerful meditation on the vagaries of politics and the pull of family"--